Race and class implications on the perceptions and management of Singapore football - Murni Nadra Abdul Rahim (2017)
Singapore football is often viewed to be a ‘Malay sport’ due to the over-representation of Malay players in the professional league. This study explores the implications of racial and class inequality in the perceptions and management of Singapore football. It asserts that despite the perceived level-playing field that sports provide; the case of Singapore football suggests that sports are not excluded from racial and class inequalities that persist in the larger society. The recognition of the power dynamics in the sport is vital to our understanding of the larger discourse on race and sports, and by association, the society in general.